Work conditions and socioeconomic inequalities in work ability - Aittomäki, Akseli; Lahelma, Eero; Roos, Eira (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The objective of this study was to investigate socioeconomic inequalities in work ability among municipal employees and the contribution of work conditions to these inequalities. ' ' METHODS ': 'The subjects were employees of the City of Helsinki and were all over 40 years of age. Data (N=1827) were collected in the age-group-based medical check-ups by occupational health personnel. Work ability was measured with a work ability index. The association between the work ability index with socioeconomic status was examined by fitting logistic regression models. ' ' RESULTS ': 'There was a consistent gradient in work ability, lower socioeconomic groups having poorer work ability. Adjusting for physical stress accounted for a substantial part of the socioeconomic inequalities. Adjusting for possibilities for influence and development at work accounted for some of the difference between white-collar and blue-collar employees, but not for differences between the white-collar subgroups among the women. Mental stress and problems in the social environment were not clearly associated with the inequalities. ' ' CONCLUSIONS ': 'Socioeconomic inequalities in work ability among municipal employees correspond to the inequalities in ill health found in general populations. Physical stress at work explained a large part of the inequality. Poor possibilities to influence one`s work contributed to the excess of lowered work ability among the blue-collar employees, but not to the inequalities between white-collar subgroups of women. Apart from physical workload, work conditions did not explain socioeconomic inequalities between white-collar subgroups of women.
Keywords: medical check-up; municipal employee; occupation; socioeconomic inequality; work ability; work characteristic; work conditions; work-related stress; workload